Counseling on Duckweed utilization as an alternative Fish feed in Cikeruh Village, Jatinangor District, Sumedang Regency - Buntora Pasaribu; Rita Rostika; Iskandar Iskandar (Farmers: Journal of Community Services, 2022)
Freshwater fish farms are sustained by the availability of economical fish feed. The rising commercial feed costs in the market are causing production challenges for freshwater fish farmers. One alternative economical fish feed that is able to substitute the commercial feed is Duckweed (Lemna sp). The purpose of this outreach activity is to educate Cikeruh community in utilizing Duckweed biomass as an alternative fish feed. The output of this research and community (PPM) service program was carried out by holding counseling activities on the use of duckweed as an alternative fish feed. Duckweed (Lemna sp) has nutritional value, rapid growth, and survives in various environmental climatic conditions. This provision will provide knowledge to the community, especially to the fish farming farmers community in Cikeruh Village that they are able to apply the duckweed biomass as an alternative fish feed to reduce the feed costs and increase their income in the future.